Modern Marriage, Men’s Extramarital Sex, and HIV Risk in Southeastern Nigeria - Smith, Daniel Jordan (© American Journal of Public Health 2007, 2007)
For women in Nigeria, as in many settings, simply being married can contribute to the risk of contracting HIV. I studied men’s extramarital sexual behavior in the context of modern marriage in southeastern Nigeria. The results indicate that the social organization of infidelity is shaped by economic inequality, aspirations for modern lifestyles, gender disparities, and contradictory moralities. It is men’s anxieties and ambivalence about masculinity, sexual morality, and social reputation in the context of seeking modern lifestyles—rather than immoral sexual behavior and traditional culture—that exacerbate the risks of HIV/AIDS.